Building the individual in economic life from the perspective of Imam Al-Baqir (peace be upon him) - (Production and consumption in Iraq) (Journal of the College of Basic Education, 2024)
The era of Imam al-Baqir (peace be upon him) is an important period and a turning point in the life of Shiites intellectually and socially. The Umayyad rulers' policy of pressure and militancy on the Shiites caused the loss of jobs, wealth, and Shia rights from the treasury. Poverty was so widespread among Shiites that imams spoke of the reward of poverty and its good effects in alleviating the suffering of Shiites. Islam is the religion of this world and the religion of the hereafter, and while recommending the reform of the hereafter, it has ordered the organization of the world. In this sense, he remained indifferent to the economic situation of his followers, and by offering very valuable solutions, he showed the direction of economic prosperity. This is how Ahl al-Bayt (peace be upon them) took care of the issue of the economy. Both tried to organize the matter themselves and invited their friends and followers to do so. Imam al-Baqir (peace be upon him) was not exempt from this rule, besides all the spiritual and upper aspects of his part, he left a rich economic image for future generations. The economy has a major role in the movement of nations and groups, in terms of growth, stability and integration, and providing them with the ability to face the difficulties that fall in the way of growth and integration, it is one of the basic factors in building civilizations and providing them with the foundations of survival and continuity, so that Islam in all its stages did not achieve its goals near or far except with the help of the economy, and money, which is the main nerve of it. Imam al-Baqir (peace be upon him) stressed in his directives and guidance to the righteous group the importance of money in the success of its work, the integrity of its affairs, and the strength of its entity.A current research acquires its importance based on the economic thought of Imam Muhammad bin Jaafar Al-Baqir (peace be upon him) and trying to increase it in analyzing the reality of production and consumption in Iraq, being one of the countries with rentier economies that depend mainly on their oil revenues significantly to cover their operational and investment expenses.